Microtechnique for serum opacity factor characterization of group A streptococci adaptable to the use of human sera. - Johnson, D R (1988)
We have developed a microtechnique for detection of streptococcal serum opacity factor (OF) and for typing of group A streptococci by inhibition of OF. This technique, which involves the use of single wells of standard 96-well tissue culture plates, offers several advantages over previous methods: no advance test preparation is required, allowing tests to be quickly and easily performed; only small quantities of reagents are required; results can be determined visually (qualitative) or by using a photometric enzyme-linked immunosorbent assay plate reader (quantitative); and human serum samples may be quickly and easily screened for OF-inhibitory antibody and subsequently used in place of difficult-to-produce and expensive hyperimmune animal sera for OF characterization of group A streptococci. Fifty-eight samples of normal adult human serum were tested by this new microtechnique for anti-OF antibodies, and 49 (84%) were found to have antibody against 1 or more of the 27 recognized OF-positive serotypes. OF antibodies to M-4, M-2, M-75, and M-48 were most common in these individuals. These 58 human serum samples collectively contained antibody to 25 of the 27 different OF-producing serotypes. Serum samples from four individuals were tested for persistence of OF antibody. OF antibodies to eight different serotypes present in the serum samples collected 7 to 12 years previously were present in the freshly collected sera, indicating that OF antibody persists in human antisera for many years. This new technique has distinct advantages and makes it possible for many laboratories to use this technique to characterize group A streptococci.